Size Constraint on Hayabusa2 Extended Mission Rendezvous Target 1998 KY26 via VLT/VISIR Nondetection - Jin Beniyama; Thomas G. Müller; Marco Delbo; Eric Pantin; Olivier R. Hainaut; Marco Micheli; Michaël Marsset (The Astronomical Journal)
1998 KY _26 is a tiny near-Earth asteroid ( H = 26.1) discovered in 1998. It has been selected as the target of the Hayabusa2 extended mission, which will rendezvous with 1998 KY _26 in 2031. However, one of the most basic physical properties, size, remains poorly constrained, posing potential challenges for spacecraft operations. We aimed at constraining the size of 1998 KY _26 by means of thermal infrared observations. We performed thermal infrared observations of 1998 KY _26 using the ESO Very Large Telescope/VISIR on three consecutive nights in 2024 May. After stacking all frames, we find no apparent detection of 1998 KY _26 on the resulting images. The upper-limit flux density of 1998 KY _26 is derived as 2 mJy at 10.64 μ m. From this upper-limit flux density obtained via non-detection, we conclude that the diameter of 1998 KY _26 is smaller than 17 m with thermophysical modeling. This upper limit size is smaller than the radar derived 30 (±10) m. Our size constraint on 1998 KY _26 is essential for the operation of the Hayabusa2 spacecraft during proximity operations using remote sensing instruments as well as a possible impact experiment using the remaining projectile.